Aprendizagem de música e inglês no canto coletivo - Carvalho, Antônio Victor Almada (2018)
The Learning of speaking and listening skills in english, within the public school, is limited to the audio activities presented in the textbook, which are not always attractive and effective. The objective of this work is to understand how it is possible to work the contents of music and English language through the collective musical practice with high school students. For that, I worked on basic vocal techniques and Singing with a group of students from the Colégio Estadual Liceu de Caucaia in rehearsals with songs by artists and bands of English speakers. It was researched in Leal (2013), Josso (2004), Souza (2014), Paviani (2008), Fazenda (1994), Federizzi (2012), Moraes (2015), Santos (2015), among others, For this work. With a focus on the study of the interdisciplinary teaching-learning process of the english language through music we will develop a qualitative research focused on a case study of a group of high school students who participate in a singing group and who holds the considerable attributes for the current research. It was verified that the human training practices occur in consonance with the work of musical training going through stages of vocal and corporal preparation, with the teaching of music aimed at memorizing a repertoire of songs chosen from a didactic proposal and methodological practices Aiming at a more playful learning of the English language. It was verified that the essay, like the presentation of the analyzed chorale, was enjoyed as a locus of teaching of music, of English and of affective practice of human values through the accentuated interaction between the students and their overcoming in the presented difficulties.